The Impact of E-commerce Platform User Reviews on Consumer Purchasing Intention – Taking Taobao as an Example, China - Hao Li; Navavongsathian, Ampol (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
With the rapid development of e-commerce and the change of consumer decision-making patterns, user reviews have become the core information medium connecting merchants and consumers, directly affecting purchasing behavior and market trust. The scale of global e-commerce transactions continues to rise, but challenges such as information asymmetry, evaluation authenticity and dynamic feedback mechanism still restrict consumer decision-making efficiency and the healthy development of platform ecology. This study takes Taobao platform users as the object and systematically explores the impact mechanism of the number, timeliness and specificity of user reviews on consumer purchase intention. 323 valid sample data were collected through questionnaire survey method. Combined with information processing theory, social identity theory and signaling theory, multiple regression analysis was used to verify the correlation between variables. The results show that the timeliness of user reviews has the most significant impact on purchase intention (Beta=0.39), followed by the specificity of the reviews (Beta=0.36), and the impact of the number of reviews is relatively weak (Beta=0.21). The study further reveals the synergistic mechanism of the evaluation system by reducing information asymmetry, reducing perceived risk and enhancing social identity. Among them, the timeliness evaluation dynamically reflects the product iteration status, the specificity evaluation improves trust through multimedia content, and the number of reviews needs to balance quality and credibility. Based on the conclusions, this paper proposes suggestions such as optimizing platform evaluation display rules, encouraging high-quality evaluation generation, and strengthening the governance of false evaluations, providing theoretical and practical guidance for e-commerce platforms, merchants, and consumers.